PROTOCOL: Effectiveness of Educational Programmes to Prevent and Counter Online Violent Extremist Propaganda in English, French, Spanish, Portuguese, German and Scandinavian Language Studies: A Systematic Review - Felipe Pathé Duarte; João Pedro Ramos; Pedro Barbosa; Matteo Vergani; Cátia Moreira deCarvalho (Campbell Systematic Reviews)
ABSTRACT This protocol outlines a systematic review that aims to understand the effectiveness of educational programmes, delivered both online and offline, designed to prevent and counter the effects of online violent extremist propaganda in multiple languages. The primary objective is to assess the impact of interventions on reducing violent extremist attitudes, beliefs and behaviours. A secondary objective is to identify key factors that influence the effectiveness of these interventions. Eligible studies will include randomised controlled trials and quasi‐experimental designs that evaluate interventions, such as media literacy initiatives, counter‐narratives, alternative narratives and gamified approaches. The analysis will synthesise outcomes using meta‐analysis and narrative synthesis, concentrating on attitudinal and behavioural extremism measures. By addressing a significant research gap, this review aims to provide actionable insights for developing educational strategies to mitigate online extremist propaganda's spread, impact and radicalising influence.